Does prophylactic tranexamic acid reduce blood loss in Indian women following vaginal delivery? - Arthi P., Nivedhana; N. R., Indu; B., Jalakandan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Postpartum hemorrhage (PPH) accounts for 25% to 33% of obstetric deaths every year. Anemia is a cause and consequence of PPH. Despite intense efforts to prevent anemia, many Indian women labour with low hemoglobin levels. Tranexamic acid (TXA), an antifibrinolytic, have been demonstrated to reduce blood loss and transfusion requirements in various surgeries including cesarean section. Objectives were to study the efficacy of TXA in effectively reducing blood loss in Indian women following vaginal delivery. Methods: This randomized, double-blind, placebo-controlled study was conducted on 200 patients scheduled for vaginal delivery. In addition to oxytocin 10 units, group T received TXA 15 mg/kg and group P received normal saline administered over 5 minutes. Estimated blood loss, Hemoglobin deficit, need for additional uterotonics, need for blood transfusion, incidence of PPH and adverse events were noted. Results: The fall in hemoglobin was significantly higher in group P (p<0.00001). Estimated 24 hour blood loss was significantly higher by a mean blood volume of 86.99 ml in group P compared to group T (p<0.00001). The incidence of PPH was lower in group T (2.8% versus 11.3%). There were no significant difference in the need for supplementary uterotonics (9.9% versus 15.5%) and the incidence of blood transfusion (2.8% versus 8.5%). No adverse maternal and fetal outcomes were noted. Conclusions: To reduce blood loss following vaginal delivery, TXA may be safely recommended as standard adjunct to Oxytocin for regular management of third stage of labour, especially in developing countries like India.